National and International Policies Governing Haze in Malaysia: a Move Forward towards a Greener Future - Abdul Shukor, Syahirah; Kamaruddin, Hanim; Imam Supaat, Dina; Mohd Khalid, Rasyikah; Hashim, Normawati (International Journal of Engineering and Technology, 2018)
Haze crisis is one of the worst disaster that ever-hit Malaysia and the neighboring countries: Singapore and Indonesia. Haze pollution caused harm to the economy and public health of the three countries. The transboundary haze caused by Indonesian forest fires consti-tutes regional and international harm. According to the Association of Southeast Asian Nations (ASEAN), the haze poses a security risk to states and human. Oil palm boom in Indonesia has sparked transboundary haze in Southeast Asia where Malaysia as one of the world largest producers of palm oils also invest in Indonesia. There have been suggestions to put up legal redress in facing the haze crisis. The suggestion of shared responsibility in cases of transboundary air pollution should be enforced by all parties for the sake of public interest. This paper examines the roles of state responsibility in dealing with air pollution and the roles of ASEAN countries in dealing with trans-boundary air pollution. It concludes with suggestion that the companies as key players in the palm oil industry also play a pivotal role in keeping the environment safe from pollution.